2017
DOI: 10.1016/j.jns.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

New diagnostic criteria for cerebral autosomal dominant arteriopathy with subcortical infarcts and leukocencephalopathy in Japan

Abstract: We propose the new criteria of high sensitivity, which will help physicians to assess the need for genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 31 publications
2
31
1
Order By: Relevance
“…Other studies have also identified mutations located outside the EGFRs implicated as the cause for CADASIL and white matter disease, suggesting that there are other mechanisms which contribute or cause the CADASIL phenotype [41,42]. The increase in mutations that do not affect Cysteine residues or the EGFRs are reflected in updated proposed guidelines for CADASIL diagnosis which suggest that non-Cysteine-altering mutations should also be investigated carefully [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also identified mutations located outside the EGFRs implicated as the cause for CADASIL and white matter disease, suggesting that there are other mechanisms which contribute or cause the CADASIL phenotype [41,42]. The increase in mutations that do not affect Cysteine residues or the EGFRs are reflected in updated proposed guidelines for CADASIL diagnosis which suggest that non-Cysteine-altering mutations should also be investigated carefully [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…While immunostaining is considered both sensitive (85-95%) and specific (95-100%), electron-microscopic testing has variable sensitivity and specificity (Joutel et al, 2001;Markus et al, 2001). However, the presence of GOMs is the pathological hallmark of CADASIL, being one of the criteria for the diagnosis, therefore its specificity can be considered 100%, while its sensitivity varies between operators (Mizuta et al, 2017).…”
Section: Diagnosismentioning
confidence: 99%
“…CADASIL is an inherited cerebrovascular disorder, whose main clinical features are migraine with aura, recurrent subcortical ischemic attacks, strokes, vascular dementia, cognitive impairment, psychiatric disturbances, and apathy [8][9][10][11][12][13][14][15][16]. Due to the rarity of the disease, CADASIL is often overlooked and misdiagnosed; nevertheless, the combined symptomatic and asymptomatic prevalence of CADASIL is estimated at least 10.7 per 100,000 adults [11,12,[17][18][19][20].…”
Section: Clinical Picturementioning
confidence: 99%
“…However, because affected family members may have been misdiagnosed [80] and de novo cases have been described [69,81], the lack of an apparent family history of CADASIL does not preclude the diagnosis. Several groups of clinicians [13,14,82] proposed suitable diagnostic strategies to be used in the clinical setting for the selection of patients to be subjected to NOTCH3 gene analysis. In fact, in order to establish a correct diagnosis, clinical signs, neuroimaging findings, and family history need to be evaluated.…”
Section: Diagnosismentioning
confidence: 99%